2022
DOI: 10.1111/1756-185x.14278
|View full text |Cite
|
Sign up to set email alerts
|

Both ASDAS and ADC are associated with spinal mobility in active axial spondyloarthritis: A comparison between early and later disease

Abstract: Objective Using diffusion‐weighted imaging (DWI)‐derived apparent diffusion coefficient (ADC), we aimed to determine the relationship between intensity of spinal inflammation and mobility in patients with axial spondyloarthritis (SpA) in early and later stages of active disease. The Ankylosing Spondylitis Disease Activity Score (ASDAS) was also used for a more comprehensive evaluation. Methods Participants with axial SpA and back pain were recruited from 10 rheumatology centers. Clinical, biochemical and radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
0
8
0
1
Order By: Relevance
“…Elsewhere, it has been found that high disease activity of AS is related to low levels of PA in patients ( 34 ). The study has shown that spinal mobility, aerobic capacity, forced vital capacity, and cardiac autonomic regulation were significantly lower in patients with AS and were associated with disease activity ( 35 37 ). Enthesitis is related to deteriorated static foot posture in patients with AS ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, it has been found that high disease activity of AS is related to low levels of PA in patients ( 34 ). The study has shown that spinal mobility, aerobic capacity, forced vital capacity, and cardiac autonomic regulation were significantly lower in patients with AS and were associated with disease activity ( 35 37 ). Enthesitis is related to deteriorated static foot posture in patients with AS ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The T2T approach is recommended for managing axSpA and aims to achieve a predefined target, typically a low DA level 12,22 . Evidence suggests that maintaining low DA is linked to a slower progression of structural damage over time 23,24 . Persistently high DA levels are associated with accelerated radiographic spinal progression in the early stage of axSpA 25 .…”
Section: Discussionmentioning
confidence: 99%
“…12,22 Evidence suggests that maintaining low DA is linked to a slower progression of structural damage over time. 23,24 Persistently high DA levels are associated with accelerated radiographic spinal progression in the early stage of axSpA. 25 Biologic treatment for axSpA patients can improve PF and spinal mobility, which may be impaired by both inflammation and structural damage, with these positive outcomes being long lasting.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that ASDAS was associated with both the extent and intensity of spinal inflammation in patients with detectable MRI inflammation only. 33 An MRI of the SI joint and/or the spine may be considered based on the physician's discretion to complement clinical and biochemical assessment at the initial stage and to provide an objective assessment of activity for disease monitoring. 34,35…”
Section: Correlation Between Clinical Disease Activity Index and Mri ...mentioning
confidence: 99%
“…However, the study showed no correlation between BASDAI and other MRI features including, chronic sacroiliitis, active axial disease, and other MRI changes (costovertebral, costotransverse, and sternoclavicular inflammation). Another study showed that ASDAS was associated with both the extent and intensity of spinal inflammation in patients with detectable MRI inflammation only 33 . An MRI of the SI joint and/or the spine may be considered based on the physician's discretion to complement clinical and biochemical assessment at the initial stage and to provide an objective assessment of activity for disease monitoring 34,35 …”
Section: Mri For Disease Activity Assessmentmentioning
confidence: 99%